Dampak COVID-19 Pada Saham Perusahaan Farmasi di Bursa Efek Indonesia: Analisis Pasar Modal Indonesia - Hartanto, Fransisca Tharia; Kusno, John Iwan (Jurusan Akuntansi Politeknik Negeri Padang, 2024)
The pharmaceutical industry has demonstrated resilience and potential for growth within the ongoing COVID-19 pandemic. Hence, pharmaceutical sub-sector stocks in Indonesia Stock Exchange emerge as a viable stock investment option for investors within the ongoing epidemic. The objective of this study is to establish empirical evidence regarding the notable market response from pharmaceutical stocks following the announcement of the first COVID-19 case in Indonesia. The research methodology employed in this study is an event study. The findings indicated a negative market reaction in one day before the first COVID-19 case was announced. On the day of the first COVID-19 case announcement, a statistically significant and favourable market response was found. Nonetheless, a negative reaction also found in H+7 after the first COVID-19 announcement. The present investigation also identified a positive cumulative abnormal return throughout the time period from H+1 to H+3, followed by a subsequent shift to a negative cumulative abnormal return from H+4 to H+7. The mixed market reaction was attributed on the market uncertainty in the beginning of COVID-19 pandemic.